Pengabaian Hak Terhadap Mantan Istri dan Anak Pasca Perceraian di Kota Makasar; Kajian Filsafat Hukum Islam - Idrus, Achmad Musyahid; Assegaf, Muhammad Rijal; Asti, Mulham Jaki; Rahman, Arif; Taudiyah, Nasya Tisfa (Jurusan Hukum Acara Peradilan dan Kekeluargaan, 2023)
The purpose of this study is to find philosophical facts about the harm of abandonment of rights of wives and children after divorce by focusing research on the reality of neglect of rights of ex-wives and children in the city of Makassar, including the causes of neglect of ex-wife and child rights and forms of handling neglect of these rights. The methods used in this study are normative and sociological approaches. The analysis used in managing this research data is by using analysis of Islamic legal philosophy. In addition to these three methods, this study also interviewed divorce perpetrators directly. The results of research in this study found that neglect of the rights of wives and children after divorce has caused harm to wives and children which has implications for economic harm, psychological harm to ex-wives and children. This study concluded that the neglect of the rights of ex-wives and children in the city of Makassar was caused by the lack of employment opportunities and lack of expertise of ex-husbands as well as the lack of responsibility of the husband's manta towards the mantas of wives and children